Analysis of Palm Oil Income and Production for Farmers Joined in Cooperatives in Pakawa Village, Pasangkayu District - Armin Armin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The agricultural and plantation sectors still play a very important role in the economy in North Mamuju Regency, the development of plantations in North Mamuju Regency is indeed very important both historically and technically. planting of plantation commodities such as cacao and oil palm. Based on these phenomena the author feels it is very necessary to look at the level of income and production among farmer community groups who are members of cooperatives, especially farmers who cultivate oil palm plants which the author sets out in a study with the title: